Pembangunan satu sistem bangunan berindustri (IBS) - lantai pasang siap sistem kepingan keluli berprofil papan kering - Norhaiza, Nordin (2014)
Previously, the Profiled Steel Sheeting Dry Board System (PSSDB) which is made up of its components of profiled steel sheeting, dry boards and screw connectors are brought separately to the site, pre-arranged and fitted together to form units in a building structure. However, to meet the needs of the Industrialised Building System (IBS) in full, the PSSDB system must be developed into a prefabricated system. The goal of this research is to develop the PSSDB system as prefabricated floor panel system installed at site that meets the characteristics of a more comprehensive IBS construction. The objective of this research is firstly; to develop a more robust floor panel system, secondly, to investigate and get the stiffness characteristics of the PSSDB floor panel connector screws; thirdly; to develop a finite element model to predict the stiffness and produce the design guidelines of PSSDB floor panels and lastly; to develop the PSSDB prefabricated floor system practically. This research is divided into three parts, mainly; laboratory testing, finite element modeling and construction of classroom cabins. Laboratory experiments consist of bending and push out tests. Bending experiment shows that the use of Cemboard dry board has increased the stiffness and ultimate load by 7.2 % and 9.1 % respectively compared to that of plywood. The addition of wood strips on the side panel has increased the stiffness by 8.8 %, ultimate load by 31.7 % and reduced the problem of uneven floor surface. Rabbet connection between two adjacent panels has allowed the panel to bear more load, which is 63.3 % of the individual panels reinforced with wooden strips and 77.6 % of unstrengthened individual panels. Semi-continuous prefabricated PSSDB floor panel has only 52% of the continuous panel stiffness. Previous finite element modeling has been expanded by comparing between the semi-loof and thick shell, uniform load and uniform line load and the distance between the profiled steel sheet and the board dry. As a result, the difference between the experimental central deflection and that of the finite element model is 7.8%. This verified model has been used to carry out a parametric study and predict the panel stiffness of a combination of several new components. These predictions are used to develop a load versus span table as a guidance to floor design. Finally, the PSSDB prefabricated floor system is applied to the construction of two classrooms cabin. Based on these findings, PSSDB floor system with its advantages is potentially suitable and safe to be used as prefabricated floor system.